Kontribusi Koperasi Merah Putih dalam Sistem Ekonomi Nasional Berbasis Pancasila - Muhammad Ridho; Hendra Riofiita (MANAJEMEN, 2026)
The Merah Putih Cooperative is a concrete manifestation of the implementation of a national economic system based on Pancasila values, particularly the principles of kinship and mutual cooperation. This article aims to examine the contribution of the Merah Putih Cooperative in strengthening the national economy through community empowerment and improving the welfare of its members using a qualitative approach with literature review (library research) from various relevant sources. The results indicate that the Merah Putih Cooperative plays a significant role in creating economic equality, expanding access to productive resources, and encouraging community economic independence. In addition, the cooperative serves as a means of instilling the values of social solidarity and economic democracy. Thus, this cooperative has a strategic contribution in realizing a national economic system aligned with Pancasila principles sustainably.